Giving Voice to Isaac: The Sacrificial Victim in Kafka's "Trial" - Ward, Bruce K. (Shofar, 2004)
One of the most enigmatic characters in modern literature is Joseph K., in Franz Kafka's The Trial. In this essay I undertake to penetrate the enigma of Joseph K. with the help of René Girard's anthropological analysis of the victim mechanism in human culture. I argue that Kafka offers us in The Trial not a parable that is (and is meant to be) utterly mystifying, but a prophetic demystification of the reality of collective persecution within the context of modernity. The particular nature of Joseph K.'s response to his persecution is highlighted by comparison with another victim in modern literature who was well known to Kafka, Dostoevsky's Dmitri Karamazov. The contrast between Joseph K. and Dmitri K. entails a discussion of Kafka's Judaism, its nature and its role in shaping both his response to the Christian art of Dostoevsky, and his own artistic revelation of the modern sacrificial victim.